A Computational Design Tool for Gradual Transition of Knit Structures in Seamless Circular Knitting. (May 2022) - Sterman, Yoav; Almog, Eli
Abstract: Computerized knitting has recently become a topic of interest for academic research. Most of the research focuses on flatbed knitting machines. However, most fabrics are usually knitted using various circular knitting technologies. This paper focuses on seamless digital knitting, a special kind of circular knitting used to create seamless garments on a knitted cylinder. This technology allows for the creation of garments with multiple knitting structures, which affects the properties and behavior of the material throughout the fabric. Existing design tools for programming seamless knitting are based on discrete definitions of zones in the fabric, which limits the design space of the knitting machines. A novel computational approach for seamless circular knitting design and programming is presented here. We created a design tool that is intended to be used by fashion and textile designers. The tool enables the creation of gradual transition between knit structures and produces organic patterns, which are extremely difficult to achieve using traditional design tools. Graphical abstract: Highlights: Smooth transitions between zones with different properties can be achieved using a computational design tool. Computational tie-dye is a sustainable process for creating patterns without going through the traditional dyeing process. Computational design tool generates random patterns that are extremely difficult to create using standard design tools. Computational design tools allow designers to skip mediators in the design workflow to engage better with knitting machines.